A study of the effects of learning style preference on achievement in a medical computer simulation. - Low GGJ (Study of the Effects of Learning Style Preference on Achievement in a Medical Computer Simulation, 1995)
The relationship of learning style performance to Neonatal Intensive Care nurses performance was examined in a computer-based medical simulation. Individuals were asked to complete a traditional paper examination, which tested their knowledge of Neonatal Advanced Life Support (NALS) resuscitation procedures. Each of the participants learning style preference was assessed through the use the Max Inventory of Learning Style Preference (M.I.L.S.) test. The individuals were then asked to take a Neonatal Advanced Life Support (NALS) computer simulation. Their achievement score and time on task were recorded. A multiple regression analysis was performed to test each of the three research hypothesis (p <.05). The first finding indicated that there was a significant correlation (p < .05) between the individuals scores on the Neonatal Advanced Life Support (NALS) achievement with the assessment scores on the Max Inventory of Learning Style Preference (M.I.L.S.) and the subjects Neonatal Advanced Life Support (NALS) pre-test score. The second finding indicated that there was not a significant correlation (p < .05) between the time on task on the Neonatal Advanced Life Support (NALS) computer simulation and learning style preference. The third finding indicated that there was a significant correlation (p < .05) between the subject's Neonatal Advanced Life Support (NALS) computer simulation and Neonatal Advanced Life Support (NALS) achievement scores with learning style preference. The results of the Max Inventory of Learning Style Preference indicated that the most popular trait was linguistic (26), followed by kinesthetic (20.62), interpersonal (18), spatial (17.29), logical (16.80) and auditory (9.64) learning abilities. The research concluded that mastery of the content knowledge was the most significant factor affecting transfer of information across different media. An individuals learning style preference was a secondary factor in achievement on a medical computer simulation. [Scientific symbols modified where possible in accordance with CINAHL policy]